(untitled) (GEOgraphia, 2009)
RESUMO As vertentes são os elementos principais da superfície terrestre e é muito importante para geógrafos que se dedicam ao estudo da geomorfologia entendê-las nos seus vários aspectos: formas das vertentes, processos de erosão e intemperismo nelas atuantes. Pode-se definir a vertente como um elemento da superfície terrestre inclinado em relação à horizontal, tendo deste modo um gradiente e uma orientação no espaço. Há vários objetivos no estudo das vertentes. Para o geomorfólogo, elas são unidades da superfície da Terra fundamentais para explicar a evolução do relevo. Os estudos das vertentes não interessam apenas aos geógrafos da disciplina geomorfologia, mas também aos engenheiros, agrônomos e outros profissionais que lidam com agricultura, mineração ou atividades afins. Contudo cada um destes profissionais só se preocupa com um aspecto particular das vertentes. O geomorfólogo é o único que tem uma visão abrangente de todos os aspectos das vertentes. ABSTRACT Hillslopes are the basic elements of all landscapes and is important for the students of geomorphology to appreciate how important they are in all aspects of the discipline. Is fundamental to geomorphology to understand forms and natural processes acting on slope facets which form almost the whole of the earth’s land surface We may define a hillslope as an element of the earth’s surface inclined to the horizontal. Thus a slope processes a gradient and an orientation in space What are the aims of hillslope studies?. To geomorphologists, hillslopes are basic landscape units and so they are fundamental to any explanation of landscape development, thus, simply describe and explain hillslopes evolution. However, hilslope studies have a much wider relevance than landscape explanation alone. Civil engineers involved with construction projects are constantly concerned with hillslope. Road gradients must not exceed acceptable standards, important question of slope stability. Landslides on embankments and cuttings shall be avoided. Agriculture on hillslopes is that mechanization is more difficult and soil erosion by flowing water is more acute, as slopes get steeper. However Engineering and agriculture sciences tend to confine their attention to specific properties of slope types. Geomorphologists are interested in ali kind of slopes, because their studies are the core of geomorphology.